The Making of a Model Refugee: Refugee Resettlement and Employment Services in Ottawa, ON - Glenen, Haley (Université d'Ottawa / University of Ottawa, 2018)
In 2015/2016, Canada accepted and resettled thousands of Syrian refugees fleeing the Syrian civil war. As a country that has for decades participated in refugee resettlement, Canada has an extensive network of settlement services available to facilitate this process. These services are developed and implemented by the Canadian state and various non-governmental organizations. This thesis focuses on Canadian employment services that are meant to facilitate the newcomers’ entrance into the Canadian labour market. Since participation in the labour market is seen as an essential step in the resettlement and integration process, employment services have also become key sites for reshaping newcomers into the desirable, self-reliant citizens. Drawing on fieldwork and semi-structured, in-depth interviews, that focus on the experience of highly professional and educated refugees (some of whom have become service providers themselves), this thesis examines the complex role employment services play in the process of refugee resettlement. To better capture how employment services facilitate this transformation, this thesis will introduce the concept of the “model refugee,” imagined as a financially stable, independent, and socially participatory citizen. By examining the barriers newcomers confront when entering the Canadian labour market, this thesis problematizes the notion that newcomers arrive in Canada destitute and uneducated and instead shows how the Canadian labour market devalues foreign credentials (a process known as ‘deskilling’). Ultimately, my research shows that a crucial aspect of becoming a “model refugee” is demonstrating a willingness to accept downward mobility and deskilling as a cost of socio-economic integration.
Keywords: Refugees; Resettlement; Integration; Labour